1999
DOI: 10.1038/sj.bjc.6690663
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the CYP17 gene is associated with male breast cancer

Abstract: SummaryThe CYP17 gene codes for the cytochrome P450c17α enzyme that is involved in the synthesis of oestrogens. This case-control study from the South East of Scotland shows that a polymorphism of the CYP17 gene is associated with an increased risk of male breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 11 publications
2
50
0
2
Order By: Relevance
“…9) The association was not observed for Caucasians in the United States, 4,5,7) in the United Kingdom, 6,10) and in Norway, 8) or Chinese in Taiwan. 11) The present study adds the finding that breast cancer risk is not high for the CC-genotype among Japanese. A meta-analysis of four studies [3][4][5][6] concluded that the relative risk was 1.5 or smaller for the CYP17 polymorphism on average.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9) The association was not observed for Caucasians in the United States, 4,5,7) in the United Kingdom, 6,10) and in Norway, 8) or Chinese in Taiwan. 11) The present study adds the finding that breast cancer risk is not high for the CC-genotype among Japanese. A meta-analysis of four studies [3][4][5][6] concluded that the relative risk was 1.5 or smaller for the CYP17 polymorphism on average.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have examined the association of the polymorphism with breast cancer risk, but the results were inconsistent. [3][4][5][6][7][8][9][10][11] Although the incidence of breast cancer in Japan is only one-fifth of that in the United States, it has been increasing since 1960s.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme has both 17-α-hydroxylase and 17,20-lyase activities, and is involved in the production of estrogen (Picado-Leonard et al, 1987). CYP17 gene polymorphisms may be related with numerous tumors, including breast cancer (Feigelson et al, 1997;Bergman-Jungestrom et al, 1999;Young et al, 1999) and prostate cancer (Habuchi et al, 2000). The CYP17 A1 allele polymorphism has an androgenic effect upon male individuals and is associated with an increased risk of prostate cancer and benign prostatic hyperplasia (Habuchi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Control DNA samples were obtained from 79 healthy males representative of the South East Scotland population. Further details of male breast cancer cases and controls have previously been described (Young et al, 1999). Ethical approval for the study was obtained through the Lothian Regional Ethics Committee.…”
Section: Case and Control Population Selectionmentioning
confidence: 99%